Pandangan Islam Terhadap Kemajuan Teknologi Informasi - Mulyanto, Agus; Akastangga, Muhammad Dedad Fajarsodiq (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2025)
Advances in information technology have brought about major changes in various aspects of human life. Rapid developments in this field include innovations in communications, education, health, economics and industry. Information technology has enabled fast and efficient access to information, increased productivity, and opened up new opportunities in an increasingly connected global world. However, behind all this progress, there are also challenges related to data security, privacy and ethics in the use of technology. In the Islamic view, information technology, like all forms of science, is a neutral tool. Islam views that technological advancements should be used for good purposes and in line with the moral and ethical values taught by religion. Technology should be utilized to strengthen social relations, spread goodness and improve the welfare of mankind, not to damage or cause destruction. The principles of sharia and maqashid sharia (the objectives of sharia) can serve as a guide in utilizing information technology to stay within the framework that is in accordance with Islamic teachings. A review of the benefits and harms of information technology shows that there are two sides that must be considered. On the one hand, this technology provides many benefits, such as increasing access to knowledge, accelerating communication, and facilitating various daily activities. On the other hand, possible harms include misuse of information, the spread of hoaxes, over-dependence, and potential moral damage if not balanced with proper control and guidance. Therefore, it is important to manage and utilize information technology wisely, in accordance with Islamic teachings that emphasize the balance between benefits and potential damage.